Dendritic cells a double-edge sword in autoimmune responses - Amodio, Giada; Gregori, Silvia (Frontiers in Immunology, 2012)
Dendritic cells (DC) are antigen-presenting cells that play a pivotal role in regulating innate and adaptive immune responses. In autoimmunity, DC act as a double-edged sword since on one hand they initiate adaptive self-reactive responses and on the other they play a pivotal role in promoting and maintaining tolerance. Thus, DC are the most important cells in either triggering self-specific responses or in negatively regulating auto-reactive responses. DC in the steady state or specialized subsets of DC, named tolerogenic DC, are involved in the latter function. Clinical and experimental evidence indicate that prolonged presentation of self-antigens by DC is crucial for the development of destructive autoimmune diseases, and defects in tolerogenic DC functions contribute to eradication of self-tolerance. In recent years, DC have emerged as therapeutic targets for limiting their immunogenicity against self-antigens, while tolerogenic DC have been conceived as therapeutic tools to restore tolerance. The purpose of this review is to give a general overview of the current knowledge on the pathogenic role of DC in patients affected by autoimmune diseases. In addition, the protective role of tolerogenic DC will be addressed. The currently applied strategies to block immune activation or to exploit the tolerogenic potential of DC will be discussed.